Peptide Receptor Radionuclide Therapy in Thyroid Cancer - Gubbi, Sriram; Koch, Christian A.; Klubo-Gwiezdzinska, Joanna (Frontiers in Endocrinology, 2022)
The treatment options that are currently available for management of metastatic, progressive radioactive iodine (RAI)-refractory differentiated thyroid cancers (DTCs), and medullary thyroid cancers (MTCs) are limited. While there are several systemic targeted therapies, such as tyrosine kinase inhibitors, that are being evaluated and implemented in the treatment of these cancers, such therapies are associated with serious, sometimes life-threatening, adverse events. Peptide receptor radionuclide therapy (PRRT) has the potential to be an effective and safe modality for treating patients with somatostatin receptor (SSTR)+ RAI-refractory DTCs and MTCs. MTCs and certain sub-types of RAI-refractory DTCs, such as Hürthle cell cancers which are less responsive to conventional modalities of treatment, have demonstrated a favorable response to treatment with PRRT. While the current literature offers hope for utilization of PRRT in thyroid cancer, several areas of this field remain to be investigated further, especially head-to-head comparisons with other systemic targeted therapies. In this review, we provide a comprehensive outlook on the current translational and clinical data on the use of various PRRTs, including diagnostic utility of somatostatin analogs, theranostic properties of PRRT, and the potential areas for future research.